Modulation of LDL receptor expression and promoter methylation in HepG2 cells treated with a Corylus avellana L. extract. (February 2019) - Benassi, Barbara; Santi, Chiara; Santangeli, Stefania; Grollino, Maria Giuseppa; Raschellà, Giuseppe; Bacchetta, Loretta; Pacchierotti, Francesca
Graphical abstract: Highlights: The hazelnut Corylus avellana L. liquid extract is not toxic to HepG2 cells. The extract modulates the expression of the DNMT3A. The extract does not trigger any change in global DNA methylation pattern. The extract stimulates the LDLR expression via promoter hypo-methylation. Abstract: The aim of our study was to evaluate the impact of an ethanolic extract of C. avellana on the molecular pathway(s) regulating the low-density lipoprotein receptor (LDLR) in HepG2 cells, mainly in terms of epigenetics. We demonstrated that viability, proliferation and cell cycle distribution were not affected up to 72 h of treatment, whereas LDLR expression was stimulated as early as 24 h following administration (P < 0.05 at 0.04 mg/ml, P < 0.01 at 0.4 mg/ml). The level of DNA Methyl Transferase 3A was up-regulated (P < 0.001 at 0.004 mg/ml, P < 0.05 at 0.4 and 4 mg/ml), without any change in global DNA methylation, whereas the percentage of 5-methyl cytosine was significantly (P < 0.05) reduced at LDLR promoter level in response to treatment (0.04 mg/ml). Overall, our data demonstrate that the ethanolic extract of C. avellana stimulates the LDLR expression in HepG2 cells by epigenetic mechanisms.